How to Manage Low Estriol Levels in Pregnancies, One Center Experience - Elif YILMAZ GULEC; Alper GEZDIRICI; Akif AYAZ; Fatma Nihal OZTURK; Ibrahim POLAT (Medeniyet Medical Journal)
Objective: Low estriol (uE3) levels in the second-trimester screening for Down syndrome may be the result of fetal demise, congenital abnormalities, or some genetic hormonal disorders of the fetus. Although X-linked ichthyosis, a microdeletion syndrome with mild ichthyosis, which causes steroid sulfatase (STS) deficiency, is the most common genetic cause, second-trimester screening tests calculate the risk for a less common and severe disorder known as the Smith Lemli Opitz syndrome (SLOS). We aimed to investigate the outcomes of pregnancies with low uE3 levels in Down syndrome screening and emphasize the high prevalence of STS deficiency instead of SLOS in such cases. Methods: Fifteen pregnancies with very low uE3 levels and high risk for trisomy and/or SLOS in screening tests were evaluated and tested for STS deficiency and SLOS. Results: Seven of the pregnancies had STS microdeletion syndrome, while additional two cases were supposed to have STS gene mutation according to family and/or postnatal history. Although one fetal death was recorded, no chromosomal abnormality, SLOS, or congenital malformation was recorded in our series. Conclusions: SLOS is a very severe and rare syndrome. The risk estimation for SLOS in screening tests causes stress for pregnant women and healthcare givers. We recommend the addition of risk estimation for STS deficiency when a low uE3 level is detected in the screening test.